How Do Discrepancies between Victimization and Rejection Expectations in Gay and Bisexual Men Relate to Mental Health Problems? - Sattler, Frank A.; Christiansen, Hanna (Frontiers in Psychology, 2017)
Introduction: Victimization and rejection expectations predict mental health problems in gay and bisexual men. Furthermore, it was shown that victimization predicts rejection expectations. Nevertheless, the levels of these two variables do not necessarily correspond as indicated by low inter-correlations, resulting in the question “How do discrepancies in the two variables relate to mental health problems?” This study tests if non-corresponding levels of victimization and rejection expectations in gay and bisexual men relate to mental health problems differently than corresponding levels of victimization and rejection expectations. It furthermore tests for linear and curvilinear relationships between victimization, rejection expectations, and mental health problems. Methods: Data from N = 1423 gay and bisexual men were obtained online. Victimization and rejection expectations were tested for discrepant values (differing .5 SD or more) and those that were in agreement (differing less than .5): 33.7% of participants were in agreement, 33.0% reported higher rejection expectations than victimization, and 33.3% v.v. Then, a polynomial regression and a surface analysis were conducted. Results: Discrepant values in victimization and rejection expectations or the direction of the discrepancy did not relevantly predict mental health problems. Findings indicate that victimization and rejection expectations predict mental health problems linearly as well as convexly (upward curving) in gay and bisexual men. Discussion: This study replicates findings that gay and bisexual men with more experiences of victimization and rejection expectations demonstrated more mental health problems. Furthermore, this study is the first one to find a convex relationship between these predictors and mental health problems, implicating that disproportionally high mental health problems exist in those gay and bisexual men with high levels of victimization and rejection expectations. discrepancies between these two variables do not predict mental health problems. Future studies are needed to test for replication of our findings.